2019
DOI: 10.3390/agronomy9050215
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Root Anatomy of Peanut (Arachis hypogaea L.) under Different Durations of Early Season Drought

Abstract: Changes in the anatomical structure of peanut roots due to early season drought will likely affect the water acquiring capacity of the root system. Yet, as important as these changes are likely to be in conferring drought resistance, they have not been thoroughly investigated. The objective of this study was to investigate the effects of different durations of drought on the root anatomy of peanut in response to early season drought. Plants of peanut genotype ICGV 98305 were grown in rhizoboxes with an interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Xylem vessel radius in particular has been observed to be highly plastic under water-deficit conditions in wheat (Triticum aestivum L.), millet (Panicum miliaceum L.), maize (Zea mays L.), and rice (Oryza sativa L.) (Han et al, 2018;Henry et al, 2012). In peanut (Arachis hypogaea L.), Thangthong et al (2019) suggested that reduction in vessel sectional area in response to water-deficit stress was due to a diminished plant growth, and this was the main factor affecting hydraulic conductance. In maize, Hazman and Kabil (2022) found that the root xylem vessels under drought were 25% smaller in size than under well-watered conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xylem vessel radius in particular has been observed to be highly plastic under water-deficit conditions in wheat (Triticum aestivum L.), millet (Panicum miliaceum L.), maize (Zea mays L.), and rice (Oryza sativa L.) (Han et al, 2018;Henry et al, 2012). In peanut (Arachis hypogaea L.), Thangthong et al (2019) suggested that reduction in vessel sectional area in response to water-deficit stress was due to a diminished plant growth, and this was the main factor affecting hydraulic conductance. In maize, Hazman and Kabil (2022) found that the root xylem vessels under drought were 25% smaller in size than under well-watered conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Water supply to the shoot of the plant depends directly on the hydraulic conductance in the root (Thangthong et al., 2019). In maize, Choudhary et al.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced stomatal length and width in comparison to controlled grown plants were also observed in all the studied Elymus species and wheat cultivars. This may be regarded as a dehydration avoidance mechanism for sustaining proper water status and reducing water loss under water deficit conditions (Xu and Zhou, 2008 ; Thangthong et al, 2019 ). Our findings are in general agreement with those previously reported by Wang et al ( 2011 ), Selim and El-Nady ( 2011 ), Petrov et al ( 2018 ), Arantes et al ( 2020 ), Chartzoulakis et al ( 2002 ), and Bosabalidis and Kofidis ( 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…But as this demand is restricted by the size of the vessels, a reduction in the RVE diameter appears to be a good alternative for the reduction of the effects of this stress. Thangthong et al [ 52 ] showed that plants under water stress have xylemic vessels of a smaller diameter and area. A reduction in the diameter of the xylemic vessels reduces the response to the high negative pressure generated by the transpiration of the leaves [ 53 ].…”
Section: Discussionmentioning
confidence: 99%